2021
DOI: 10.1021/acs.jproteome.1c00638
|View full text |Cite
|
Sign up to set email alerts
|

Biofluid Metabolomics of Mice Exposed to External Low-Dose Rate Radiation in a Novel Irradiation System, the Variable Dose-Rate External 137Cs Irradiator

Abstract: An important component of ionizing radiation (IR) exposure after a radiological incident may include low-dose rate (LDR) exposures either externally or internally, such as from 137 Cs deposition. In this study, a novel irradiation system, VAriable Dose-rate External 137 Cs irradiatoR (VADER), was used to expose male and female mice to a variable LDR irradiation over a 30 d time span to simulate fall-out-type exposures in addition to biofluid collection from a reference dose rate (0.8 Gy/min). Radiation marker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(23 citation statements)
references
References 61 publications
1
22
0
Order By: Relevance
“…Interestingly, xanthurenic acid, a product of tryptophan catabolism, may show differential effects from dose rate. Identification in LDR studies typically show reduced urinary concentrations [6,8,27,28], however, here we observed an increase at 1 d. A slight decrease occurred here at 7 d (reference FC = 0.8) highlighting our previous conclusions that involvement of the host microbiota and diet in producing tryptophan metabolites will complicate their use in biodosimetry panels. Increased levels of trigonelline were only observed in the VHDR 1 d cohort (p < 0.001, VHDR FC = 1.2), but for both doses at 7 d (p < 0.001, reference FC = 1.4, VHDR FC = 1.3).…”
Section: Figuresupporting
confidence: 44%
See 4 more Smart Citations
“…Interestingly, xanthurenic acid, a product of tryptophan catabolism, may show differential effects from dose rate. Identification in LDR studies typically show reduced urinary concentrations [6,8,27,28], however, here we observed an increase at 1 d. A slight decrease occurred here at 7 d (reference FC = 0.8) highlighting our previous conclusions that involvement of the host microbiota and diet in producing tryptophan metabolites will complicate their use in biodosimetry panels. Increased levels of trigonelline were only observed in the VHDR 1 d cohort (p < 0.001, VHDR FC = 1.2), but for both doses at 7 d (p < 0.001, reference FC = 1.4, VHDR FC = 1.3).…”
Section: Figuresupporting
confidence: 44%
“…Increases were observed at 1 d in compounds typically identified post-irradiation, including carnitine (p < 0.001, reference FC = 2.4, VHDR FC = 1.9), TML (p = 0.006, VHDR FC = 1.3), and xanthurenic acid (p < 0.001, reference FC = 1.3, VHDR FC = 1.3) (Figure 2, Table 1). All three of these metabolites have been identified in a previous study analyzing urine from mice exposed to low-dose rate IR (≤1 Gy/day) and reference dose rate exposures [8], as well as several other studies examining post-irradiation effects on urinary signatures [15,16]. TML, and carnitine in particular, are among the most consistently altered metabolites post-irradiation and indicate perturbation to fatty acid β oxidation.…”
Section: Figurementioning
confidence: 76%
See 3 more Smart Citations